Higher CPAP levels improve functional residual capacity at birth in preterm rabbits - Martherus, T; Croughan, MK; Crossley, KJ; Wallace, MJ; McGillick, EV; Thio, M; Roehr, CC; Pearson, JT; Lee, K; Ruben, G; Kitchen, MJ; Te Pas, AB; et al. (Springer Nature, 2021)
Background: Preterm infants are commonly supported with 4–8 cm H2O continuous positive airway pressures (CPAP), although higher CPAP levels may improve functional residual capacity (FRC).